Analisis Strategi Pemasaran Digital Terintegrasi dan Implementasi Tren Omnichannel Terhadap Perilaku Konsumen di Indonesia - Sekarsari, Dewi; Sudrajat, Ajat; Muslihat, H. Asep (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
The development of digital technology has driven significant changes in how consumers interact and transact with brands. This study aims to analyze the influence of integrated digital marketing strategies and the implementation of omnichannel trends on consumer behavior change in Indonesia. The research employed a quantitative approach through the distribution of questionnaires to active digital platform users. The results indicate that both variables significantly affect consumer decision-making, preferences, and loyalty. These findings highlight the synergy between digital and physical channels in effectively meeting modern consumer expectations.